Analisis Hubungan Penerapan RULA dengan Produktivitas Kerja Karyawan Office Warehouse Perusahaan Pakan Ternak - Prasetyo, Ahmad; Windyatri, Hasyrani; Pradipto, Gigih Hapsak (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to analyze the relationship between work posture, assessed using the Rapid Upper Limb Assessment (RULA) method, and the work productivity level of employees in the office warehouse division of a livestock feed company. A quantitative approach with a cross-sectional design was employed, involving 14 respondents. Data were collected through posture observations using the RULA worksheet and a productivity questionnaire covering aspects of performance and personality. The evaluation results showed that all employees had RULA scores ranging from 3 to 4, indicating a moderate ergonomic risk level. Meanwhile, work productivity scores varied from 57.4 to 78.6. Statistical analysis using the Chi-Square test produced a significance value of 0.730, indicating no statistically significant relationship between RULA scores and employee productivity. Nevertheless, ergonomic improvements are still recommended to prevent musculoskeletal disorders and to enhance long-term work comfort and efficiency.